STRESS WITH THE INCIDENCE OF HIPERTENSION COMPLICATIONS TO PATIENTS WITH HYPERTENSION - Prawesti, Dian; Prasetyorini, Hesty Titis (Jurnal Penelitian STIKES Kediri, 2012)
Hypertension can be controlled if it is treated properly from its early stage. However, many hypertensive patients are too late to realize until they experience complication of hypertension. Many things can cause complications of hypertension such as stress. Stress triggers hormonal producing which increase blood pressure and result complications of hypertension. The design of this research was cross sectional in which the independent and dependent variable were assessed simultaneously at one time. The population was hypertensive inpatients at wards Kediri Baptist Hospital that met criteria inclusion. Using Accidental Sampling, it was obtained 29 respondents. The independent variable was stress and the dependent variable was incidence of hypertensive complication. The data were collected using questionnaire and structured observation. Further, the data were analyzed statistically using Chi-Square with significant level Î± â‰¤ 0.05. It could be concluded that there was a correlation between stress and incidence of hypertensive complication on adult inpatient wards at Kediri Baptist Hospital.